Prospects in the utilization of assisted reproductive technologies (ART) towards improved cattle production in Nigeria - Oguejiofor, C. F. (Nigerian Journal of Animal Production, 2020)
Cattle production and the beef and dairy industry are important sources of financial revenue for the government and the individual farmers and employees involved in livestock husbandry. Nigeria has a huge potential for cattle production but sadly this has been poorly developed. The estimated national cattle population of 19 million is grossly inadequate in meeting the national human demand for meat, milk and other cattle products or in contributing to the gross domestic product. The low cattle productivity is partly attributable to the poor utilization of assisted reproductive technologies (ART) in dairy and beef cattle breeding and production. These technologies generally include oestrus synchronization, artificial insemination (AI), multiple-ovulation and embryo transfer (MOET), in vitro fertilization (IVF), sex determination, cloning and genetic engineering. ART have been applied extensively in the yearly production of millions of cattle in many developed and developing countries worldwide. This review highlights the applications and potentials of ART in cattle production and suggests how stakeholders in the Nigerian cattle industry can exploit these potentials. It is clear that the utilization of ART will enhance national livestock productivity so that Nigeria can feed her growing population and possibly increase her foreign exchange earnings by becoming a livestock-exporting country.